Larger Descemetorhexis to Improve Graft Adhesion in Descemet Membrane Endothelial Keratoplasty Does Not Cause Postoperative Peripheral Corneal Edema - Tourtas, Theofilos; Weller, Julia M.; Bachmann, Björn; Kruse, Friedrich (Eye & Contact Lens-Science and Clinical Practice, 2015)
To evaluate the incidence of peripheral corneal edema after Descemet membrane endothelial keratoplasty (DMEK) with respect to the size of the descemetorhexis.A single-center retrospective review of data of 200 consecutive DMEK surgeries for Fuchs endothelial dystrophy was performed. Forty-eight eyes of 47 patients were enrolled in this study based on the presence of a peripheral zone of free denuded stroma between the margin of the graft and the host's Descemet membrane (DM) (group A) or a peripheral overlap between the graft and the host's DM (group B). In group A (n=26 eyes), the diameter of the descemetorhexis was approximately 10 mm, whereas in group B (n=22 eyes), the diameter was approximately 6 mm. Both groups received an 8-mm graft. Main outcome measures included peripheral corneal thickness (PCT) at 4 mm from the center, central corneal thickness (CCT), central-to-peripheral thickness ratio (CPTR), and endothelial cell density (ECD).Mean preoperative PCT±SD in group A was 728±52 ?m and in group B was 708±49 ?m (P=0.192). Four weeks after DMEK, mean PCT±SD was 703±43 ?m in group A and 691±59 ?m in group B (P=0.368). Mean preoperative CCT±SD was 642±53 ?m and 627±58 ?m in groups A and B, respectively (P=0.306). There was no significant difference in CCT between groups A and B 4 weeks after surgery (P=0.268). Mean preoperative CPTR±SD in group A was 0.88±0.05 and in group B was 0.89±0.05 (P=0.934). Four weeks after DMEK, CPTR was not significantly different between groups A and B (P=0.893). There was no significant difference in ECD between groups A and B, before and at 4 weeks after DMEK (P=0.093 and P=0.831, respectively).A larger descemetorhexis in DMEK resulting in a peripheral small zone of denuded stroma does not increase the incidence of peripheral corneal edema as compared with a small descemetorhexis with overlapping DMs.
EVALuna2:21238